2016
DOI: 10.1186/s12917-016-0689-5
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro method to test the safety and efficacy of low-level laser therapy (LLLT) in the healing of a canine skin model

Abstract: BackgroundLow-level laser therapy (LLLT) has been used clinically as a treatment modality for a variety of medical conditions including wound-healing processes. It is an attractive and emerging method to enhance wound healing and improve clinical outcomes both in human and veterinary medicine. Despite the fact that the use of LLLT continues to gain in popularity, there is no universally accepted theory that defends all its cellular effects and beneficial biological processes in tissue repair. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…The ideal laser energy density (J/cm 2 ) and treatment frequency delivered to incisions and wounds are unknown. Lower energy settings may not have any remedial effect on the wound; however, higher energy settings have been shown to be detrimental to wound healing . Authors of in vitro studies using human fibroblasts and in vivo studies assessing rat wounds have suggested that 0.5‐5 J/cm 2 stimulates healing, whereas >10 J/cm 2 may be inhibitory .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ideal laser energy density (J/cm 2 ) and treatment frequency delivered to incisions and wounds are unknown. Lower energy settings may not have any remedial effect on the wound; however, higher energy settings have been shown to be detrimental to wound healing . Authors of in vitro studies using human fibroblasts and in vivo studies assessing rat wounds have suggested that 0.5‐5 J/cm 2 stimulates healing, whereas >10 J/cm 2 may be inhibitory .…”
Section: Discussionmentioning
confidence: 99%
“…Authors of in vitro studies using human fibroblasts and in vivo studies assessing rat wounds have suggested that 0.5‐5 J/cm 2 stimulates healing, whereas >10 J/cm 2 may be inhibitory . Using canine keratinocytes, authors of a recent in vitro study found increased cellular migration and proliferation at 0.1, 0.2, and 1.2 J/cm 2 and detrimental effects at 10 J/cm 2 . It is not known how these findings translate into in vivo healing because of the many variables that could affect healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Lasers are known to induce biphasic dose responses (BDR), namely; biostimulation and bioinhibition responses. 11 This effect is related to an increase in adenosine triphosphate (ATP) in the mitochondria that produce deoxyribonucleic acid (DNA) and ribose nucleic acid (RNA) and whose synthesis increases after laser diode irradiation. This increase can cause cellular responses to injury through the production of proteins associated with repair and healing processes.…”
Section: Introductionmentioning
confidence: 99%
“…A laserterapia de baixa intensidade já é reconhecida como um método de tratamento eficaz para cicatrização de tecidos. Vários estudos in vitro e in vivo têm mostrado ações positivas na perfusão tecidual e estimulo à neovascularização, proliferação fibroblástica e queratinócitos, aumento na síntese e deposição de colágeno e hidroxiprolina, diminuição de mediadores inflamatórios como IL-1β, IL-10, TNF-α e NF-κB, diminuição do estresse oxidativo e aceleração da cura tecidual [7,9,[12][13][14][15].…”
Section: Discussionunclassified